Transformation of humic substances by the freshwater Ascomycete Cladosporium sp. - Rojas Jiménez, Keilor Osvaldo (2017)
The ecological relevance of fungi in freshwater ecosystems is becoming increasingly evident, particularly in processing the extensive amounts of polymeric organic carbon such as cellulose, chitin, and humic substances (HS). We isolated several fungal strains from oligo‐mesotrophic Lake Stechlin, Brandenburg, Germany, and analyzed their ability to degrade polymeric‐like substrates. Using liquid chromatography‐organic carbon detection, we determined the byproducts of HS transformation by the freshwater fungus Cladosporium sp. KR14. We demonstrate the ability of this fungus to degrade and simultaneously synthesize HS, and that transformation processes were intensified when iron, as indicator of the occurrence of Fenton reactions, was present in the medium. Furthermore, we showed that structural complexity of the HS produced changed with the availability of other polymeric substances in the medium. Our study highlights the contribution of freshwater Ascomycetes to the transformation of complex organic compounds. As such, it has important implications for understanding the ecological contribution of fungi to aquatic food webs and related biogeochemical cycles.